Core vocabulary intervention for an isiXhosa-English speaking child with speech sound difficulties. Issue 4 (2nd October 2018) - Pascoe, Michelle; Rossouw, Kate; Mahura, Olebeng
Abstract: In this paper we describe speech difficulties observed in a bilingual child (aged 3 years, 0 months at the time of assessment) acquiring isiXhosa and English in South Africa. Speech difficulties were noted in both Ntando's languages, but as is currently common in urban South Africa, the child's family favoured intervention focusing on his English and the clinician-researcher was a first language English speaker with limited isiXhosa. We investigated whether core vocabulary is an approach that can be effectively used by clinicians when a mismatch between the languages of client and clinician occurs. We describe the way in which the approach was implemented and the speech outcomes for both languages. Parental and teacher responses to the Intelligibility in Context Scale showed perceived differences in pre- and post-intervention responses. Accuracy of Ntando's speech, as measured by percentage consonants correct (PCC), increased for both his English and isiXhosa, and his consistency improved for English. We reflect on the challenges and opportunities associated with using a core-vocabulary approach when working with bilingual children.